Partial redundancy of the pattern recognition receptors, scavenger receptors, and C-type lectins for the long-term control of Mycobacterium tuberculosis infection. - Court, N; Vasseur, V; Vacher, R; Frémond, C; Shebzukhov, Y; Yeremeev, V; Maillet, I; Nedospasov, SA; Gordon, S; Fallon, P; Suzuki, H; Ryffel, B; et al. (2010)
Mycobacterium tuberculosis is recognized by multiple pattern recognition receptors involved in innate immune defense, but their direct role in tuberculosis pathogenesis remains unknown. Beyond TLRs, scavenger receptors (SRs) and C-type lectins may play a crucial role in the sensing and signaling of pathogen motifs, as well as contribute to M. tuberculosis immune evasion. In this study, we addressed the relative role and potential redundancy of these receptors in the host response and resistance to M. tuberculosis infection using mice deficient for representative SR, C-type lectin receptor, or seven transmembrane receptor families. We show that a single deficiency in the class A SR, macrophage receptor with collagenous structure, CD36, mannose receptor, specific ICAM-3 grabbing nonintegrin-related, or F4/80 did not impair the host resistance to acute or chronic M. tuberculosis infection in terms of survival, control of bacterial clearance, lung inflammation, granuloma formation, and cytokine and chemokine expression. Double deficiency for the SRs class A SR types I and II plus CD36 or for the C-type lectins mannose receptor plus specific ICAM-3 grabbing nonintegrin-related had a limited effect on macrophage uptake of mycobacteria and TNF response and on the long-term control of M. tuberculosis infection. By contrast, mice deficient in the TNF, IL-1, or IFN-gamma pathway were unable to control acute M. tuberculosis infection. In conclusion, we document a functional redundancy in the pattern recognition receptors, which might cooperate in a coordinated response to sustain the full immune control of M. tuberculosis infection, in sharp contrast with the nonredundant, essential role of the TNF, IL-1, or IFN-gamma pathway for host resistance to M. tuberculosis.